Can economic crises be good for your diet? - Ralitza Dimova; Ira N. Gang; Monnet Benoit Patrick Gbakou; Daniel Hoffman (Institute for the Study of Labor (IZA), 2011)
With fortuitously timed data - collected before, during and after a major macro-financial crisis in Bulgaria - we revisit several hypotheses in the economics and nutritional literature related to the tendency of households to smooth their nutritional status over time. We explore the dietary impact of both falling real incomes in the context of hyperinflation and crisis and changing relative prices and the changing responsiveness of different groups of people to these incomes and prices over six year of fundamental structural reforms of the economy. Our results highlight large and dramatically changing food and nutrient elasticities, which challenge the perception of household ability to smooth their nutrient stream during economic crises and transitions.
urn:nbn:de:101:1-201104134505
Keywords: E320; I120; P230; P240; P360; 330; crisis; diet; fluctuation; health; nutrition; Ernährung; Nahrungsmittelkonsum; Übergangswirtschaft; Wirtschaftskrise; Bulgarien